Development of a Test Kit for Screening of Arsenic in Medicinal Plant Products - Leuprasert, Lagsana; Chawengrattanachot, Watinee (Journal of Health Science of Thailand, 2017)
Arsenic is highly poisonous metal that may contaminate in medicinal plant products through plant food chain, product additives and the environment. The arsenic contamination could be either intentional for alleged medicinal or accidental purposes. This research was aimed at providing a simple test instrument for identification of arsenic level in medicinal plant products in order to ensure human safety. Arsenic test kit was developed on the basis of Gutzeitีs reaction that generated arsine gas and then reactively captured with silver nitrate impregnated chromatography paper and detected as colored chemical compound of arsine and silver nitrate reaction which was compared to a developed standard arsenic color tab. The detection limit of this test kit was 0.4 part per million (ppm or milligram per kilogram) that was below the maximum acceptable level of arsenic contamination- 4 ppm concentration as specified by Thai Food and Drug Administration (FDA). The developed test kit was assessed for validation of method through an inter-laboratory comparison which included 124 samples of medicinal plant products using graphite furnace atomic absorption spectrometry as a conventional standard method. The validation test reported; sensitivity, specificity and accuracy to be 85.71, 86.46 and 86.29 respectively. Satisfaction of the users of test kit was also evaluated. On practical usefulness, 80.95 percent were highly satisfied and 19.05 percent were moderately satisfied. The kit utilization; convenience, accessories and packaging satisfaction of users were rated by 51.52 percent of them to be highly satisfied, 25.76 percent moderately satisfied and 22.72 percent less satisfied. Regarding the procedure, 56.6 percent found the kit to be highly satisfied, 37.72 percent moderately satisfied and 5.68 percent less satisfied. The analysis took only 10 minutes and the procedure could be easily followed. This arsenic test kit is therefore appropriate for product quality control by medicinal plant product manufacturers and for consumers protection by traditional medical practitioners, general traditional practitioners, traditional pharmacists, traditional midwives and responsible non-technicians from public and private agencies.